2019
DOI: 10.1002/chem.201903572
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of α‐Amino Phosphonic Acids using Stable Imino Phosphonate as a Universal Precursor

Abstract: A practical method for synthesizing chiral α‐amino phosphonic acid derivatives was developed. Readily available and stable N‐o‐nitrophenylsulfenyl (Nps) imino phosphonate was utilized as a substrate for a highly enantioselective Friedel–Crafts‐type addition of indole or pyrrole nucleophiles catalyzed by chiral phosphoric acid. The resulting adduct was easily converted into N‐9‐fluorenylmethyloxycarbonyl (Fmoc) amino phosphonic acid, which is useful for synthesizing peptides containing an amino phosphonic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…As a part of our research to develop organocatalytic reactions, we reported the kinetic resolution of 1,2- trans -cycloalkanediols via asymmetric acylation catalyzed by chiral N-heterocyclic carbenes (NHCs). The kinetic resolution of the diol proceeds with high enantioselectivity (selectivity factor, s = 218) with catalytic amounts of the chiral NHC precursor ent - 1a and 4-dimethylaminobenzoic acid in the presence of 1,8-bis­(dimethylamino)­naphthalene (proton sponge) and 2-bromo-3-phenylpropanal 2 (Scheme ). The use of the carboxylic acid as an additive significantly increases the reaction rate and the enantioselectivity of this reaction.…”
Section: Introductionmentioning
confidence: 99%
“…As a part of our research to develop organocatalytic reactions, we reported the kinetic resolution of 1,2- trans -cycloalkanediols via asymmetric acylation catalyzed by chiral N-heterocyclic carbenes (NHCs). The kinetic resolution of the diol proceeds with high enantioselectivity (selectivity factor, s = 218) with catalytic amounts of the chiral NHC precursor ent - 1a and 4-dimethylaminobenzoic acid in the presence of 1,8-bis­(dimethylamino)­naphthalene (proton sponge) and 2-bromo-3-phenylpropanal 2 (Scheme ). The use of the carboxylic acid as an additive significantly increases the reaction rate and the enantioselectivity of this reaction.…”
Section: Introductionmentioning
confidence: 99%
“…As a part of our research to develop organocatalytic reactions, [17][18][19][20][21][22][23][24][25][26][27] we recently reported the kinetic resolution of αhydroxythioamides using asymmetric acylation catalyzed by chiral N-heterocyclic carbenes [28] (NHCs). [29][30][31][32] In the previous study, we found that the kinetic resolution of thioamide 2 a showed slightly better selectivity (selectivity factor, s = 11) than that of the corresponding amide 1 a (s = 7) in the presence of 2bromo-3-phenylpropanal (3), [33,34] chiral NHC precursor 4 a, [35] 1,8-bis(dimethylamino)naphthalene (proton sponge), and 4-dimethylaminobenzoic acid (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Reaction with pyrroles 1 afforded the corresponding phosphonic acids 66 in good ee's, employing chiral BINOL‐derived phosphoric acid XV (Scheme 31). [51] When N ‐substituted pyrroles 1 were used yields dropped off dramatically.…”
Section: Organocatalytic Fca Reactions Of Pyrrolesmentioning
confidence: 99%